Theories of International Politics and Zombies : Apocalypse Edition - Drezner, Daniel W. (Book collections on Project MUSE., 2022)
"How international relations theory can be applied to a zombie invasionWhat would happen to international politics if the dead rose from the grave and started to eat the living? Daniel Drezner's groundbreaking book answers the question that other international relations scholars have been too scared to ask. Addressing timely issues with analytical bite, Drezner looks at how well-known theories from international relations might be applied to a war with zombies. Exploring the plots of popular zombie films, songs, and books, Theories of International Politics and Zombies predicts realistic scenarios for the political stage in the face of a zombie threat and considers how valid-or how rotten-such scenarios might be.With worldwide calamity feeling ever closer, this new apocalyptic edition includes updates throughout as well as a new chapter on postcolonial perspectives"--